(untitled) (Bangladesh Journal of Neuroscience, 2019)
Polyneuropathy is an initial presentation and essential feature of POEMS ( polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes) syndrome. Neuropathy is typically distal, symmetric and slowly progressive with demyelinating changes. After a gradual proximal spread, it usually results in severe muscle weakness and functional disabilities. In the present report, we describe a 40-year-old diabetic male presented with gradually progressive weakness of both lower limbs for 1 year followed by the involvement of both upper limbs for the last 3 months. On examination hyperpigmentation, lymphadenopathy, gynecomastia, anasarca, hepatomegaly, bilateral optic disc swelling, sensory-motor polyneuropathy was found. Laboratory findings showed IgG lambda monoclonal gammopathy, raised VEGF, sensory-motor demyelinating and axonal polyneuropathy. All findings were consistent with POEMS syndrome. The patient was treated with lenalidomide and dexamethasone cyclical therapy with some clinical improvement. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 51-56